The Association of Peroxisome Proliferator-Activated Receptor δ and Additional Gene-Gene Interaction with C-Reactive Protein in Chinese Population - Ding, Xiao-Ying (Int J Endocrinol, 2016)
Aims. To examine the association between 4 single nucleotide polymorphisms (SNPs) of peroxisome proliferator-activated receptors δ (PPARδ) polymorphisms and C-reactive protein (CRP) level and additional gene-gene interaction. Methods. Line regression analysis was performed to verify polymorphism association between SNP and CRP levels. Generalized multifactor dimensionality reduction (GMDR) was employed to analyze the interaction. Results. A total of 1028 subjects (538 men, 490 women) were selected. The carriers of the C allele (TC or CC) of rs2016520 were associated with a significant decreased level of CRP, regression coefficients was −0.338, and standard error was 0.104 (p = 0.001). The carriers of the G allele (CG or GG) of rs9794 were also significantly associated with decreased level of CRP, regression coefficients was −0.219, and standard error was 0.114 (p = 0.012). We also found a potential gene-gene interaction between rs2016520 and rs9794. Subjects with rs2016520-TC or CC, rs9794-CG or GG genotypes have lowest CRP level, difference (95% CI) = −0.50 (−0.69 to −0.21) (p < 0.001), compared to subjects with rs2016520-TT and rs9794-CC genotypes. Conclusions. rs2016520 and rs9794 minor allele of PPARδ and combined effect between the two SNP were associated with decreased CRP level.